2018
DOI: 10.21147/j.issn.1000-9604.2018.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Clinical laboratory and imaging evidence for effectiveness of agarose-agarose macrobeads containing stem-like cells derived from a mouse renal adenocarcinoma cell population (RMBs) in treatment-resistant, advanced metastatic colorectal cancer: Evaluation of a biological-systems approach to cancer therapy (U.S. FDA IND-BB 10091; NCT 02046174, NCT 01053013)

Abstract: The correlations of the tumor marker, tumor volume and SUV changes on PET-CT, and LDH levels themselves, and with OS, support the concept of a biological response to RMB implantation and the validity of the biological-systems approach to mCRC. A phase III clinical trial is planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…CEA and CA19-9 are the most common and convenient preoperative serological indicators for colorectal cancer. These markers reflect the occurrence, development, and differentiation of tumor cells and tissues and provide important reference information for clinical diagnosis, classification, and prognosis evaluation ( 31 ). MRI characteristics of rectal cancer combined with CEA and CA19-9 can significantly improve preoperative T and N staging accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…CEA and CA19-9 are the most common and convenient preoperative serological indicators for colorectal cancer. These markers reflect the occurrence, development, and differentiation of tumor cells and tissues and provide important reference information for clinical diagnosis, classification, and prognosis evaluation ( 31 ). MRI characteristics of rectal cancer combined with CEA and CA19-9 can significantly improve preoperative T and N staging accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…While the surgery for all animals was minimally invasive, it was not identical to the planned laparoscopic approach intended in the clinical situation. In clinical trials of macrobeads made from similar agarose and of similar size, but comprised of murine adenocarcinoma cells for the treatment of various cancers, we have used a laparoscopic implant technique that allowed visualization and disbursement of the macrobeads within the peritoneal cavity, as an outpatient procedure 74,75 . Although combined safety and efficacy studies have the benefit of reducing overall numbers of animals in accordance with the 3Rs (replacement, refinement, reduction), a limitation of our combined approach is that experimental manipulation to assess the test article from the efficacy perspective may have influenced safety as it relates to understanding the tissue–macrobead interface.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the gene products induced by the pathway have the capability to induce epithelial-mesenchymal transition (EMT) and promote cell regeneration. , Cancer stem-like cells (CSCs) enable tumor cells to self-renew and undergo unlimited proliferation and differentiation . Studies have shown the presence of rare subpopulations of stem cells within solid tumors that exhibit resistance to chemotherapy or radiotherapy . The high self-renewal ability of CSCs enables them to contribute to tumor recurrence following treatment .…”
Section: Introductionmentioning
confidence: 99%
“… 18 Studies have shown the presence of rare subpopulations of stem cells within solid tumors that exhibit resistance to chemotherapy or radiotherapy. 19 The high self-renewal ability of CSCs enables them to contribute to tumor recurrence following treatment. 20 One of the primary challenge in this field is to identify specific markers that can effectively recognize CSCs.…”
Section: Introductionmentioning
confidence: 99%